2022
DOI: 10.53854/liim-3004-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of COVID-19 on tuberculosis

Abstract: During COVID-19 pandemic, a lot of diseases suffered from a limited access to health care services, owing to the use of resources, both technical and financial, mainly directed towards such a dramatic outbreak. Among these, tuberculosis (TB) has been one of the most penalized, with a huge delay both in diagnosis and in start of treatment, with a consequential dramatic increase in morbidity and mortality. COVID-19 and tuberculosis share similar common pathogenetic pathways, and both diseases affect primarily th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In conclusion, we suggest that TB should be actively ruled out when confronting migrants with recurrent insidious headache, abdominal pain, or back pain, with or without nonspecific chronic symptoms or unexplained weight loss and several prior visits. This is now especially relevant, since it is expected that the major impact of COVID-19 on TB incidence and mortality would be much larger in 2022 and beyond ( 32 ). Supplementary Figure S1 in Appendix 2 includes a chart for clinicians describing the prototypical profiles of patients studied which might help them to screen extra-pulmonary of dTB.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we suggest that TB should be actively ruled out when confronting migrants with recurrent insidious headache, abdominal pain, or back pain, with or without nonspecific chronic symptoms or unexplained weight loss and several prior visits. This is now especially relevant, since it is expected that the major impact of COVID-19 on TB incidence and mortality would be much larger in 2022 and beyond ( 32 ). Supplementary Figure S1 in Appendix 2 includes a chart for clinicians describing the prototypical profiles of patients studied which might help them to screen extra-pulmonary of dTB.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that reported a positive trend of TB has been reversed due to the COVID-19 pandemic outbreak. They expected that the unintended consequences of COVID-19 preventive measures such as restriction and reduced access to healthcare resulted in a drop in access to TB services [ 25 ]. The predictive models have also reported that the negative impact of COVID-19 on TB is much larger [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) remains a major public health problem and ranks second as the leading cause of death by a single infectious disease globally after COVID-19 [ 1 ]. In 2021 alone, an estimated 10.6 million new cases and 1.6 million deaths were attributed to TB globally [ 2 ].…”
Section: Introductionmentioning
confidence: 99%